Development of diagnosis and treatment in the iliotibial band syndrome - Pawlina, Mateusz; Pawełczak, Natalia; Oskroba, Aleksander; Orzechowska, Aleksandra; Ziętara, Karolina; Stawikowski, Cezary; Zielonka, Bartłomiej; Kowalczyk, Ilona; Pawłowski, Piotr; Raksa, Karolina (Journal of Education, Health and Sport, 2023)
Introduction and objective: The iliotibial band (ITB) is a complex structure located in the lateral part of the thigh and consists of longitudinally arranged fascial connective tissue. The aim of this study is to analyze the current literature regarding etiology, epidemiology, diagnosis, and conservative treatment of iliotibial band syndrome (ITBS). Materials and methods: PubMed database were searched. The criteria for qualifying the article for the review were the following keywords: running, iliotibial band syndrome, knee injuries, conservative treatment, physical therapy modalities. 11 articles from 2017 to 2022 were analyzed. The searches included systematic reviews, meta-analyses, randomized controlled trials, and review articles. Description of the state of knowledge: Iliotibial band syndrome is the most common cause of lateral knee pain in runners and cyclists. It is presumably caused by excessive tension in the iliotibial band. Excessive tension is the result of overuse disorder of the lateral knee. Key symptom of ITBS is sharp or burning pain in the region of the lateral femoral epicondyle.. Pain typically occurs during physical activity, after a reproducible time or distance of running. The diagnosis is achieved through taking clinical history and physical assessment. Summary: Treatment of ITBS is based on therapeutic exercise, manual therapy, neuromuscular re-education, modalities and anti-inflammatory medications. Eliminating modifiable risk factors helps prevent ITBS from recurring.